THE CONSTRAINTS OF CROSS-LINGUISTIC TRANSFER ON BIPA LEARNING - Riki Nasrullah; Iwan Koswara; R. Yudi Permadi (Universitas Padjadjaran, 2022)
One of the interesting issues regarding the BIPA learning process is how the similarities and differences of the source and target languages (Indonesian language) are related to students’ understanding of the Indonesian language. This study is related to what is known as a cross-linguistic transfer. This paper reviews theoretically cross-linguistic transfer in learning in BIPA (Indonesian Language for Foreign Speakers). This study employed the descriptive-qualitative method. A qualitative method was used to describe the patterns of similarity between Indonesian language as the target language and the learner’s native language in BIPA learning using a cross-linguistic transfer approach. The result of the study revealed that the discussion about cross-linguistic transfer in the process of learning the Indonesian language for Foreign Speakers (BIPA) was not a monolithic matter. The similarities and differences in word forms and word meanings were closely related to how quickly speakers of other languages learned the target language.